Wax‐Transferred Hydrophobic CVD Graphene Enables Water‐Resistant and Dendrite‐Free Lithium Anode toward Long Cycle Li–Air Battery. Issue 16 (3rd June 2021) - Ma, Yong; Qi, Pengwei; Ma, Jun; Wei, Le; Zhao, Liang; Cheng, Jian; Su, Yanhui; Gu, Yuting; Lian, Yuebin; Peng, Yang; Shen, Yanbin; Chen, Liwei; et al.
Abstract: One of the key challenges in achieving practical lithium–air battery is the poor moisture tolerance of the lithium metal anode. Herein, guided by theoretical modeling, an effective tactic for realizing water‐resistant Li anode by implementing a wax‐assisted transfer protocol is reported to passivate the Li surface with an inert high‐quality chemical vapor deposition (CVD) graphene layer. This electrically conductive and mechanically robust graphene coating enables serving as an artificial solid/electrolyte interphase (SEI), guiding homogeneous Li plating/stripping, suppressing dendrite and "dead" Li formation, as well as passivating the Li surface from moisture erosion and side reactions. Consequently, lithium–air batteries fabricated with the passivated Li anodes demonstrate a superb cycling performance up to 2300 h (230 cycles at 1000 mAh g −1, 200 mA g −1 ). More strikingly, the anode recycled thereafter can be recoupled with a fresh cathode to continuously run for 400 extended hours. Comprehensive time‐lapse and ex situ microscopic and spectroscopic investigations are further carried out for elucidating the fundamentals behind the extraordinary air and electrochemical stability. Abstract : Water‐resistant Li anodes are developed by implementing a wax‐assisted transfer protocol to passivate the Li surface with high‐quality CVD graphene. Serving as an artificial solid/electrolyte interphase, the hydrophobic, conductive, and robust graphene coating can effectively dissipate local surface charges, homogenize Li deposition, suppress dendrite growth, and protect the Li surface from parasitic reactions with organic electrolytes and moisture.